Sustainable Management of Madidihang Fisheries (Thunnus albacares) in Morotai Island District - Kodobo, M. Jihar; Irham, Irham; Ahmad, Adityawan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to measure and determine the sustainability status of the yellowfin tuna (thunnus albacares) in a sustainability perspective according to ecological, economic, social, technological, and legal/institutional dimensions in Morotai Island District. The method used in this study is a descriptive method with an analytical tool, namely RAPFISH analysis. Based on the analysis, sustainability on ecological and economic dimensions, yellowfin tuna (thunnus albacares) fishery has a moderately sustainable status with an average sustainability index value of 53.78 and 68.77 respectively. On the social and technological dimensions, the status is less sustainable with an average index score of 49.99 and 46.26, respectively. For the legal and institutional dimensions, it has a good sustainability status with an average index value of 76.13. Based on its status, it is also known which attributes are the priority (focus) in the development of multi-dimensional yellowfin fishery (Thunnus albacares) in Morotai Island Regency. These attributes are migration distance and collapse degree for the ecological dimension; entry and employment restrictions for the economic dimension; new arrivals and family participation for the social dimension; use of FAD's and pre-sale processing for the technology dimension; Illegal Fishing for legal and institutional dimensions.